History of Esophagogastric Junction Cancer Treatment and Current Surgical Management in Western Countries - Berlth, Felix (J Gastric Cancer, 2019)
The incidence of esophagogastric junction (EGJ) cancer has been significantly increasing in Western countries. Appropriate planning for surgical therapy requires a reliable classification of EGJ cancers with respect to their exact location. Clinically, the most accepted classification of EGJ cancers is “adenocarcinoma of the EGJ” (AEG or “Siewert”), which divides tumor center localization into AEG type I (distal esophagus), AEG type II (“true junction”), and AEG type III (subcardial stomach). Treatment strategies in western countries routinely employ perioperative chemotherapy or neoadjuvant chemoradiation for cases of locally advanced cancers. The standard surgical treatment strategies are esophagectomy for AEG type I and gastrectomy for AEG type III cancers. For “true junctional cancers,” i.e., AEG type II, whether the extension of resection in the oral or aboral direction represents the most effective surgical therapy remains debatable. This article reviews the history of surgical EGJ cancer treatment and current surgical strategies from a Western perspective.